0044 The Circadian System Modulates Cardiovascular Responses To Standing Differently In People With Obstructive Sleep Apnea Compared To Healthy Controls. (12th April 2019) - Thosar, Saurabh S; Butler, Matthew P; Bowles, Nicole P; McHill, Andrew W; Berman, Alec M; Herzig, Maya X; Stewart, Alicia V; Roberts, Sally A; Clemons, Noal A; Morimoto, ki; Emens, Jonathan S; Shea, Steven A
Abstract: Introduction: Adverse cardiovascular (CV) events occur most commonly at ~9 AM in the general population, but ~3 AM in people with obstructive sleep apnea (OSA). Standing up after a night of sleep generates changes in blood pressure (BP) and heart rate (HR) and autonomic activation. We tested whether the CV reactivity to standing is different in OSA versus healthy controls (HC) across all phases of the circadian cycle. Methods: 21 HC (age: 52±7 [mean±SD] years) and 8 OSA (age: 48±7 years; AHI range 15-74.1) participants with similar body mass indices completed a 5-day forced desynchrony (FD) protocol with 10 identical recurring 5 h 20 min sleep/wake cycles in dim light. Twenty-five minutes after awakening and continued supine rest, participants stood up. Systolic BP, diastolic BP and HR were measured during supine rest and after one min of standing at all circadian phases. Salivary melatonin was used as a circadian phase marker. Data were analyzed using mixed-model cosinor analyses. Results: While supine, mean HR was higher in OSA but there were no mean differences in BP between groups, and no group by circadian phase interactions for BP or HR. Similarly, there were no significant mean group differences upon standing in the changes in BP or HR (first minute CV reactivity; p>0.05). However, upon standing, the circadian time of the peak increase in diastolic BP was significantly different in OSA versus HC (peaks at circadian phases corresponding to ~11PM and ~1PM respectively, p=0.008). And there was a trend for systolic BP reactivity to be different in OSA versus HC (peaks at ~6AM and ~4PM respectively, p=0.059). There was no evidence of a group by phase interaction for HR reactivity to standing. Conclusion: In this preliminary analysis, the peak circadian phase of diastolic BP reactivity to change in posture differs between OSA and HC. These results may have implications for differences in time of adverse CV events in OSA and the general population. Support (If Any): NIH R01-HL125893; CTSA UL1TR000128